A quasi-experimental study of parent and child well-being in families of color in the context of COVID-19 related school closure. (March 2022) - Ursache, Alexandra; Barajas-Gonzalez, R. Gabriela; Adhikari, Samrachana; Kamboukos, Dimitra; Brotman, Laurie M.; Dawson-McClure, Spring
Abstract: Families of color living in historically disinvested neighborhoods face a multitude of health disparities which have been exacerbated by COVID-19 and the resulting strategies to mitigate its transmission. School closure, which occurred with little warning and few, if any, resources for preparation, disrupted multiple aspects of families' lives; these disruptions are anticipated to adversely impact mental health and well-being. The current study aims to advance understanding of the experiences of families of young children of color during the pandemic by utilizing a natural experiment design to test impact on child and parent mental health and sleep in the context of COVID-19 related school closure among families in historically disinvested neighborhoods. Data from this study come from an ongoing study of 281 families of color enrolled in 41 pre-kindergarten (pre-K) programs in neighborhoods across New York City (NYC). In NYC, school closure occurred on March 16, 2020, during a data collection period involving phone surveys with parents; the quasi-experimental design allows for comparison of the 198 families who had completed the survey prior to March 16, and the 83 families who completed the survey after March 16, using identical protocols and procedures. Results demonstrate poorer mental health among parents surveyed after school closure as compared to before school closure. No differences were found for parent sleep, child mental health, or child sleep. Implications of this work highlight the need for structural and systemic supports for families faced with compounding stressors as a result of the COVID-19 pandemic and related school closure. Highlights: We use a natural experiment to examine impact of COVID-19 and related school closure. We do so among families of color living in historically disinvested neighborhoods. We examine impacts on parent and child mental health and sleep. Results demonstrate that parents report poorer mental health after school closure.